A FACTOR ANALYSIS OF SUSTAINABILITY PRACTICES AND HALAL PRACTICES IN THE COFFEE INDUSTRY: A Study on the Supply Chain of Kopi Kenangan Indonesia - Kuncorosidi Kuncorosidi (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2026)
The coffee industry in Indonesia is experiencing rapid growth but faces sustainability challenges such as deforestation, agrochemical use, and production waste. At the same time, there is an increasing demand for halal-compliant products, driven by Indonesia’s position as a leader in the global halal economy. This position is supported by three key factors: a large Muslim population, growing awareness of the halal lifestyle, and strong government support for the development of the halal industry. This study aims to identify the factors that influence sustainability and halal practices and to construct a factor model for both. The research method used is quantitative with a confirmatory factor analysis (CFA) approach. Data was collected through questionnaires distributed to consumers of Kopi Kenangan. The results show that there are 11 indicators forming five main factors in sustainability practices and 5 indicators forming four main factors in halal practices. In conclusion, consumer perception of sustainability and halal practices plays a crucial role in strengthening ethical and sustainable business strategies for the company